The synergy of Islamic da’wah and Madura culture programmes on Nada FM Sumenep Radio, Indonesia - Achmad, Zainal Abidin; Ida, Rachmah; Mustain; Lukens-Bull, Ronald (Penerbit Universiti Kebangsaan Malaysia, 2021)
Nada FM Sumenep radio is the only commercial radio in East Java that has successfully synergised Islamic religious programmes and Madurese culture in its broadcasts. Several things influenced that success. This includes a careful understanding of business opportunities, ingenuity in creating programmes that fit the needs of religious content for Sumenep residents, Islamic da'wah programme that is synergised with Madurese culture, and the support of communication technology (mediamorphosis). This qualitative research method uses virtual ethnography, where researchers conducted participant observation in the real and virtual world. The informants are one cultural leader, two programmers, one announcer, and three loyal listeners. This research explored the process of mediamorphosis, types of Islamic da'wah programmes, and Madurese cultural programmes, content, and the form of interaction among listeners and radio institutions in a networked society. The results showed that the form of mediamorphosis of Nada FM radio can be seen through the usage of streaming, Facebook, Twitter, Instagram, and WhatsApp. The aim of synergising content is to strengthen Islamic religious beliefs while maintaining Madurese culture. Connectivity in a networked society makes it easier to gain access to the radio content. Listeners prefer using WhatsApp as the media to express criticism. The ad suitability, chat duration, announcers' attitude, quality of sound and streaming, and the suitability of the da'wah theme are also key reasons to the success of Nada FM Sumenep radio.